Frailty as the Cornerstone of Elderly Care: Strategies for Early Detection and Intervention - Abu (Magyar Gerontológia, 2025)
Frailty is increasingly recognized as a cornerstone of elderly care. It represents a multidimensional syndrome of vulnerability that increases risks of disability, hospitalization, institutionalization, and mortality.